2021
DOI: 10.1016/j.psychres.2021.114107
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and Covid-19 in prison: Empirical findings from 2016 to 2020 in a Swiss prison

Abstract: Disadvantaged populations have an increased risk of suicide and suicide attempts because of the Covid-19 pandemic. To date, few studies focused on people living in detention, who have a high burden of mental health problems and are exposed to severe control measures. Our study investigated whether there was an increase in suicide attempts in prison. Data were collected in the largest Swiss pre-trial prison (Champ-Dollon) for the pre-pandemic and the pandemic periods. We identified a statistically significant 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
1
16
0
2
Order By: Relevance
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
“…The prevalence ratio of suicide attempt reported by 30 non-clinical samples ranged from 0.333 to 6.261, and the pooled prevalence ratio under the random effect model was 1.14 (95% CI: 1.053–1.233; p = 0.001), indicating that suicide attempts were more prevalent during the COVID-19 pandemic than during pre-pandemic periods ( Figure 4 ). Though effect sizes were substantially heterogenous among the samples ( I 2 = 99.996%, tau 2 = 0.036, P Q < 0.05), a sensitivity analysis using the leave-one-out method or by excluding lower quality studies [ 66 ] showed that the increased trend of suicide attempts was robust ( Figures S6 and S7 ). Through visual inspection of the funnel plot ( Figure S8 ) and the non-significant results of the Egger’s tests ( intercept = 6.52, t = 0.17, p = 0.865), no publication bias among the non-clinical samples was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 13 Although effectively shielding incarcerated individuals from SARS-CoV-2 entering prisons, these measures triggered revolts and may have worsened the mental health of prison residents. 8 , 13 , 22 Since June 2020, containment measures were progressively relaxed in community and prison settings, with various degrees of limitation to interprison and prison/community movement being maintained throughout the period. Also, the rates of incarceration, occupancy, and overcrowding returned to pre–COVID-19 levels during the second epidemic wave, possibly increasing the overall risk of virus introduction and spreading within prison facilities.…”
Section: Discussionmentioning
confidence: 99%
“…And they know everything's shutdown and they're, like, 'what's going to happen to me?' Finally, a study of reported self-harm events in a people in a Swiss prison from 2016 to 2020 found that comparing 2016-2019 to 2020, there was a 57% increase in severe suicide attempts from 4.4/100 people in detention/year to 7.0/100 people in detention/year, and a 57% increase in other self-harm events from 7.9/100 people in detention/year to 12.5/100 people in detention/year [84].…”
Section: Plos Onementioning
confidence: 99%